Legal Justice and Legal Accountability in Multi-Clause Franchise Disputes (Case Study: Saimen Sarolangun) - Theodore P.Z.M.G.Sibarani; Mohammad Jamin (Dinasti Research, 2025)
Currently, the business world is rapidly growing, as evidenced by the increasing application of business development through franchise systems widely adopted by entrepreneurs in Indonesia. The economic development of society in this technological era has certainly undergone various changes, resulting in business relations becoming more accessible to everyone. Therefore, adequate legal protection is needed to minimize potential problems that may arise, aiming to ensure justice and legal certainty within society. This means that the development of the business world must be accompanied by strong and sufficient legal protection to support potential legal issues in the future. In other words, regulations that provide legal justice and effective dispute resolution methods are required, which will particularly impact the parties involved, especially those who suffer losses, along with clear legal accountability so that violators can be held responsible for their actions. This research is normative legal research with a conceptual approach, and the data collection techniques used include literature study and a case study on decision No. 25/Pdt.G/2022/PN Srl. The findings show that dispute resolution in the case was carried out through litigation efforts, proving that the defendant committed a breach of contract in a franchise agreement that had already been notarized. This indicates that the franchise agreement was drafted by the parties into a legal document with strong evidentiary value. The document clearly establishes the legal relationship between the parties regarding their rights and obligations, created to ensure legal justice and to prevent future disputes. Furthermore, legal accountability was addressed in the judgment’s ruling, which was considered sufficient to cover all losses suffered by the plaintiff.